Comparison of Intraocular Pressure Changes Due to Exposure to Mobile Phone Electromagnetics Radiations in Normal and Glaucoma Eye - Shokoohi-Rad, Saeed (Middle East Afr J Ophthalmol, 2020)
PURPOSE: The aim of this study is to investigate the effects of electromagnetic waves (EMWs) emitted by a mobile phone on the intraocular pressure (IOP) in the eyeball. METHODS: This quasi-experimental study was conducted on 166 eyes from 83 individuals in the 40–70 age range who referred to “Khatam-al-Anbia Hospital, Mashhad, Iran” in 2016. There were two groups of participants, and the first one consisted of 41 participants who had normal eyes, whereas the second one comprised 42 participants who suffered from open-angle glaucoma disease. The IOP in both groups was measured and recorded by a specialist before and after talking 5 min on the cellphone with the help of the Goldman method. Statistical analysis such as paired t-test and analysis of variance was performed and all tests are statistically significant at (P < 0.05). For this purpose, the SPSS software (version 16) was applied. RESULTS: IOP in the glaucoma eye (42 eyes) ipsilateral to mobile phone before and after the intervention was 18.64 ± 6.7 and 23.53 ± 6.3, respectively (P < 0.001). However, IOP in the control group (41 eyes) ipsilateral to mobile phone before and after the intervention was 12.95 ± 3.5 and 13.39 ± 2.8, respectively (P = 0.063). IOP change in the opposite glaucomatous eye to mobile phone in glaucoma group (39 eyes) and normal group (44 eyes) was not significantly different before and after the phone call (P = 0.065 and P = 0.85, respectively). CONCLUSION: We found that the acute effects of EMWs emitted from the mobile phones can significantly increase the IOP in glaucoma eye, while such changes were not observed in normal eyes.